A LARGE-SCALE, ASYNCHRONOUS, WEB-BASED MSW COMPREHENSIVE EXAM ADMINISTRATION: OUTCOMES AND LESSONS LEARNED. - Patterson, David A. (Journal of Social Work Education)
Described is the administration and outcomes of an asynchronous. Web-based, comprehensive exam covering MSW foundation curriculum. Over a 48-hour period of test availability, 198 students completed the 4-hour-long exam composed of 100 randomly generated questions. Significant differences in student performance across college locations were found. A post-examination survey found a large majority of students were able to easily access the online exam, found the testing tool easy to use, and were able to complete the comprehensive exam with little difficulty. The future use of online assessment for the comprehensive exam was supported by 87% of respondents.